Poéticas da Existência: o caminho da razão poética no pensamento zambraniano - Lustosa, Naiana dos Anjos (2021)
The Zambranian appealing to an integrating poetic reason capable of recovering the “mysterious nexus” that unites us and reality finds an echo that gradually intensifies, gaining considerable spaces of attention in philosophy nowadays. However, it is not always easy to orient yourself in the writing of this author, who, attracted by the writing of poetic inspiration, offers us an enigmatic language even now, despite the relative work of the commentators. Little known, it seduces us with the invitation to penetrate a ground with a lack of indications. In order to make her affective contributions, she wrotes texts that open up an immense field of interpretations and faces, in any case, the problem of establishing the coordinates for this thinking - a circumstance that could determine the place of her thought and the time of your word. This work seeks to answer a challenge, to raise the voice of this thinker. Such an attempt is to promote the exchange of readings taken from different points of view and from the development of the different aspects that marked the author's work, in the sense of creating a path where metaphors are reconciled to give body to the philosopher's proposal: the poetic reason. This will happen, first, from the elaboration of the author's writing, pointing to her trajectory that calls for the union between life and thought, besides considering the writing of poetic inspiration and, to a certain extent, mystical. Then, a return to Socrates and Plato will be made to understand the dimension of dialogue and words, rescuing the author's exile to understand the dimension of the human from the return to the cave. Finally, we have the method used by the author for poetic reason, established from an interpretative turn of the Cartesian method, ending with some conclusions.